The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/23311975.2018.1564168
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tweet Form’s effect on users’ engagement on Twitter

Abstract: This research focuses on the effects on users' engagement of different tweet forms including text length, text sentiment and the usage of hashtag, mention, video or picture URL. In the first part, we analyze the tweets of five companies from the apparel industry and finds out that there is no universal form that can boost user's engagement, but in company scale, the effects of different forms between companies are various due to company attributes. Hence, in our second research, we expand the dataset and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
(10 reference statements)
2
22
0
Order By: Relevance
“…Text length: While some scholars found the relationship between text length and engagement, some research indicates that longer text could get more attention [ 80 ]. For example, an organization’s lengthy tweet could significantly reduce the negative sentiment of customers’ tweets [ 81 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Text length: While some scholars found the relationship between text length and engagement, some research indicates that longer text could get more attention [ 80 ]. For example, an organization’s lengthy tweet could significantly reduce the negative sentiment of customers’ tweets [ 81 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tweets absent a photo (10) received less engagement (2.7%) than those that included a photo [90 (4.7%)], consistent with other reports (Barton et al, 2017;Chung, 2017;Zhang et al, 2020) that show visual content can improve engagement. However, Han et al (2019) found that audience preference may also play a role in desire for photos, videos, and hashtags. A few of the non-photo tweets (n = 6) included a GIF meme, used as a humorous placeholder when a specific photo was not available.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Schreiner et al, 2019 found that content characteristics and emotion in social media could have an impact on user engagement behavior. Similarly, Han et al's (2019) study empirically revealed the associations between types of social media messages and user engagement levels. This study attempts to this kind of effect, i.e.…”
Section: Research Modelmentioning
confidence: 89%
“…Prior literature indicates that users' responses to social media could be influenced by content of messages (e.g. Glazer, 2012;Han et al, 2019;Schreiner et al, 2019). For example, Schreiner et al, 2019 found that content characteristics and emotion in social media could have an impact on user engagement behavior.…”
Section: Research Modelmentioning
confidence: 99%